A Working Model of Mentors’ Contributions to Youth Mentoring Relationship Quality: Insights From Research on Psychotherapy (LEARNing Landscapes, 2012)
Mentoring is a flexible approach to youth development that can promote positive outcomes through informal learning. Not all mentoring relationships are beneficial, however, as lower quality mentoring relationships tend to have little effect. A mentor’s overall approach to the relationship has been found to influence relationship quality. But what does it take to engage a young person in such a relationship and sustain it over time? In this paper, I draw from the research on psychotherapy and other related literatures to briefly sketch out a working model for the determinants of mentoring relationship quality and then focus in detail on one of these—the contributions of the mentor.
Keywords: Mentoring; youth development; informal learning; relationship; psychotherapy